The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/flan.12192
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Mean in Spanish Writing: A Case Study of a Genre‐Based Pedagogy for Standards‐Based Writing Instruction

Abstract: This case study reports the results of a genre-based approach, which was used to explicitly teach the touristic landmark description to fourth-grade students of Spanish as a foreign language. The instructional model and unit of instruction were informed by the pedagogies of the Sydney School of Linguistics and an instructional model for integrating the three modes of communication, as well as the literature on content-based instruction. An analysis of the writing of a focal student, Jackie, provides evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 29 publications
2
29
0
2
Order By: Relevance
“…Specifically, the data show that explicit instruction was needed on the stages and the linguistic features of the recount—content, organization and cohesion, and tone—to support students’ production of culturally informed recounts. This result echoes the findings of earlier studies in other FL and second language contexts in the United States, such as Byrnes () and Ryshina‐Pankova () in the FL university context; Troyan (, ) in the early FL education context; de Oliveira and Lan (), Ramos (, ), Schleppegrell (), and Schulze () in the L2 context; and Colombi () in the university‐level heritage language speakers context.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, the data show that explicit instruction was needed on the stages and the linguistic features of the recount—content, organization and cohesion, and tone—to support students’ production of culturally informed recounts. This result echoes the findings of earlier studies in other FL and second language contexts in the United States, such as Byrnes () and Ryshina‐Pankova () in the FL university context; Troyan (, ) in the early FL education context; de Oliveira and Lan (), Ramos (, ), Schleppegrell (), and Schulze () in the L2 context; and Colombi () in the university‐level heritage language speakers context.…”
Section: Discussionsupporting
confidence: 88%
“…In the elementary school FL context, Troyan (, ) analyzed the differences between beginning students’ descriptions of a historical monument in Spanish prior to the genre‐based instruction and their descriptions following the instruction, which unsurprisingly demonstrated their increased control over the linguistic features that expressed register in that particular genre.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Others, however, deliberately took on proficiency frameworks and their limited potential for developing a sense “of what it takes to communicate capably across, or for that matter, even within cultures” (Warford & White, , p. 401). Crane (), Maxim (), and Troyan (), for example, proposed organizing the FL curriculum according to a genre‐ and discourse‐based orientation that would reflect a social understanding of language in use through a careful selection of written and oral texts appropriate for each level.…”
Section: From Literacy To Multiliteracies In Fl Educationmentioning
confidence: 99%
“…For example, Rifkin () concluded that “two decades of guideline‐influenced instruction have failed to have an impact on student learning” (p. 582). For this reason, we require more work investigating the validity of these tools, following the lead of Dandonoli (), Norris and Pfeiffer (), Troyan (, ), and Tigchelaar, Bowles, Winke, and Gass (). If we are using those tools as indicators and starting points for goal‐setting, then we must validate them and identify their limitations in order to more effectively guide student language development.…”
Section: Defining Grand Challenges In Foreign Language Educationmentioning
confidence: 99%